Management of thrombocytopenia-associated multiple organ failure: plasma infusion vs plasma exchange - Çeleğen, Mehmet; Çeleğen, Kübra (The Turkish Journal of Pediatrics, 2022)
Background. Thrombocytopenia-associated multiple organ failure (TAMOF) causes a high ratio of mortality in pediatric patients. Only anticoagulants and profibrinolytic molecules can be replaced with plasma infusion (PI), while therapeutic plasma exchange (TPE) eliminates antifibrinolytic and thrombogenic molecules and charges inadequate anticoagulants and profibrinolytic molecules. This study aims to compare the efficacy of plasma exchange to plasma infusion in pediatric TAMOF patients. Methods. Twenty-seven patients with TAMOF were included and the efficacy of PI and TPE was compared. The demographic data, admission laboratory values, Pediatric Logistic Organ Dysfunction (PELOD) scores before the beginning of treatment and PELOD at the end of treatment, and outcomes of groups were compared. Results. Sixteen children were in the plasma infusion group, eleven children were in the plasma exchange group. The total mortality rate of all patients was 37%. The PELOD scores were significantly reduced on the 5th day of treatment in both groups and also PELOD scores were significantly higher on the 5th day of study in the non-survivor group (p: < 0.001). The fifth day of PELOD scores and ferritin had a significant effect on mortality (OR: 1.85, 95% CI: 1.02-2.69; p: 0.04, OR: 1.43, 95% CI: 0.97-2.03; p: 0.05). The overall mortality ratio was not different between TPE and PI groups (p: 0.12). Conclusions. Although there was no difference in mortality rates in children who received plasma exchange compared to children who received plasma infusion, mechanical ventilation and length of pediatric intensive care unit (PICU) day were shorter in the TPE group. The small patient population may be the major cause for the lack of significant statistical difference.
Keywords: pediatric; pediatric logistic organ dysfunction; plasma exchange; plasma infusion; thrombocytopenia-associated multiple organ failure